Proactive Mechanism of Protection against SQL Injection Attack (International Journal of Scientific Research and Management (IJSRM), 2015)
In this fast growing environment most of the organizations are now computerized and those are not seeking computerization. As the use of computer increases the need of the database is also increasing and hence the database security is very important aspect. Various types of attackers and database hackers are trying everything to break the security of the database and to spoof the information contained in the database. The SQL Injection Attack is a very big security threat in the modern databases. An attacker tries to exploit faulty application code by causing maliciously crafted database queries. The attackers are allowed to obtain unauthorized access to the backend database by submitting the malicious SQL query segment to change the intended application. Various database researchers and practitioners provide different approaches to prevent from SQLIA but none of the approach is fully capable to. In this paper we propose some methods of protection against SQL injection attack.